2014
DOI: 10.1002/jcph.247
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic characterization of baclofen in patients with chronic kidney disease: dose adjustment recommendations

Abstract: The pharmacokinetics of baclofen is well delineated in subjects with normal kidney function (KF); however, pharmacokinetics data in patients with chronic kidney disease (CKD) are not and dosage recommendations remain empirical. The effects of CKD on baclofen pharmacokinetics were assessed through a multi-center, open-label, single 5-mg dose, pharmacokinetics study. The KF was measured as the creatinine clearance (CrCL) calculated with the Cockroft-Gault (C-G) equation or as the estimated glomerular filtration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Similarly, to the study of Marsot et al , an influence of CLCr was observed on baclofen CL/F but without significantly improving the fit. The impact of renal failure has been clearly described by Vlavonou et al showing that the systemic clearance of baclofen was reduced by 34, 49 and 63% in mild, moderate and severe renal failure, respectively. A reduction of 1/3, 1/2 and 2/3 of the baclofen daily dose in patients with mild, moderate and severe renal failure was advised to achieve baclofen exposure comparable to that observed in healthy subjects with normal renal function.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, to the study of Marsot et al , an influence of CLCr was observed on baclofen CL/F but without significantly improving the fit. The impact of renal failure has been clearly described by Vlavonou et al showing that the systemic clearance of baclofen was reduced by 34, 49 and 63% in mild, moderate and severe renal failure, respectively. A reduction of 1/3, 1/2 and 2/3 of the baclofen daily dose in patients with mild, moderate and severe renal failure was advised to achieve baclofen exposure comparable to that observed in healthy subjects with normal renal function.…”
Section: Discussionmentioning
confidence: 90%
“…In healthy volunteers a high correlation between the apparent renal clearance of baclofen and the creatinine clearance was described ( 12 ). This has been confirmed by a study including four groups of patients with different kidney disease stages ( 30 ). The authors found the following significant linear relationship ( R 2 = 0.67, p < 0.0001) between baclofen clearance (CL/F) and creatinine clearance (CrCL):…”
Section: Metabolism and Eliminationmentioning
confidence: 56%
“…9 However, this report does not consider the potential difference in pharmacokinetics for a patient who is on chronic baclofen therapy. [2][3][4][5][6]10 It is unclear if depot lipophilic stores of drug or the chronic saturation of plasma protein and tissuebinding sites is the mechanism responsible for the reported toxicities in this patient population. Moreover, patients with severe chronic renal disease have been reported to have increased susceptibility to baclofen toxicity, despite levels that are within defined "range."…”
Section: Discussionmentioning
confidence: 99%